التوجيهات النبوية في تربية الشباب : دراسة ميدانية تحليلية لمعهد دار السلام كنتور إندونيسيا - Ahmad Fathurrahman Ghozali (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
Educating the youth has always been a key priority for educators not only in the modern era but also throughout all ages of human history because they- the youth-are believed to be the Ummah's future leaders and its source of uprightness. The approach of educating these young people, thus, should be carried out in accordance with prophetic guidelines if it is to be effective. Prophetic Educational Guidelines are inspired by divine revelation. In them are solutions to recurrent problems encountered by young people as well as answers to predicaments faced by modern educational system in the modern erathe young generation of the prophetic era are a self-evident to this. They were the ones who carried the torch of Islam whose light has lit up to this day. Prophetic Educational Guidelines, nonetheless, have been confined to libraries and academia, which makes some people confused and believe that it is impossible to apply such guidelines in today's societies of young generation. In fact, it makes them believe that such prophetic principles are inadequate in educating the youth of today. Hence, this research is an attempt to address to this question and remove the misgivings claiming that the application of Prophetic Educational Guidelines is far-fetched and impossible. This research uses two approaches: a field study of Dar Al-Salam Institute with special focus on its educational curricula and on how they are applied to its young students. Likewise, it uses an analytical approach to examine and analyze Prophetic Educational Guidelines in educating the youth of all age categories, thus, prove the validity of its educational content in the said institute and its applicability in the modern time by adopting several methods in applied education. The research has concluded a number of findings, the most important of which are: that it is possible to apply Prophetic Educational Guidelines to all age categories, that Dar Al-Salam Institute is successful in applying such principles whereby its graduates are deemed influential in various social domains in the Indonesian society; that Prophetic Educational Guidelines are the most effective in terms of addressing numerous domains: religious, behavioural, psychological, and practical. Finally, this study refutes all the misgivings that presuppose the impossibility of adopting Prophetic Educational Guidelines. It disproves all the myths assuming that the content of Prophetic Educational Guidelines is obsolete and inappropriate for the modern era, thus, cannot provide answers to its recurrent issues and developments, neither cope with its rapidly changing pace. Contrary to all these doubts and misgivings, Prophetic Education is all-inclusive and flexible taking into account all social classes, all circumstances, and all situations.